Impact of sodium-glucose cotransporter-2 inhibitors on kidney outcomes in type 2 diabetes: A tertiary center experience - Mohammed H Tawhari; Raed A Aldahash; Faisal M Almutairi; Mahdi S Albogami; Ahmad E Rokon; Faisal A Alsomali; Khaled H Alanazi; Abdulrahman A Alshehri; Talal H Almutairi; Abdulrahman D Alharbi; Rayan M Alghamdi; Ibrahim H Tawhari; et al. (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Diabetic nephropathy (DN) is a complication of chronic hyperglycemia associated with diabetes mellitus (DM). Several studies have demonstrated the positive impact of sodium-glucose cotransporter-2 (SGLT2) inhibitors on kidney outcomes. The objective of the study was to evaluate the effects of dapagliflozin, an SGLT2 inhibitor, on kidney outcomes in Saudi patients with type 2 DM. MATERIALS AND METHODS: Study included all Saudi patients with type 2 DM who visited our center from August 1, 2021, to July 31, 2022, and had been on dapagliflozin for at least 3 months. Data was abstracted through chart review for all patients included in the study. Paired t-test or Wilcoxon signed-rank test were used to compare the results before and after treatment for continuous variables and the McNemar test was used to compare the results for categorical data. RESULTS: Study included 184 Saudi patients with type 2 diabetes with a mean age of 61.32 years (SD=9.37). Dapagliflozin 10 mg/day significantly reduced hemoglobin A1C (HbA1C) from a mean (SD) of 9.00 to 8.40 (P < 0.001). Among a subgroup of patients with significant proteinuria (n = 83), dapagliflozin significantly reduced ACR from a median of 93.1 to 64.9 mg/g (P = 0.001). Following treatment, the estimated glomerular filtration rate improved from a mean of 69.83 to 71.68 mL/min and the mean arterial pressure (MAP) fell from 90.03 to 89.06 mmHg, both were not statistically significant. Despite a statistically insignificant increase in the episodes of urinary tract infections (UTIs), the hospitalization rate declined. No episodes of amputations or ketoacidosis occurred during the study period. CONCLUSION: SGLT2 inhibitors had beneficial effects among Saudi patients with type 2 diabetes by improving diabetic control and lowering proteinuria. Dapagliflozin did not result in significant harm, including UTIs, amputations, and ketoacidosis.